Forms of Intra-School Project Harvesting Implementation SMA Negeri 9 Padang - Nailathul Fadhila; Wimbrayardi (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to determine and describe the form of intra-school project harvesting implementation of SMA Negeri 9 Padang. This study used qualitative research descriptive approach. The researcher's own research instruments and assisted by supporting instruments in the form of stationery and mobile phones. Data collection techniques include observation, interviews, literature studies and documentation. Data is analyzed by collecting data, identifying data, classifying data, clarifying and inferring data. The results showed that the form of implementation of the intra-school project harvest of SMA Negri 9 Padang had been carried out well, but there were several things in the implementation before carrying out the project the principal gave more briefing on what exactly the harvest of this project was, many of these teachers were still confused about the implementation of this project harvest because it was still called a new curriculum. Debriefing for this new curriculum must be provided so that teachers and students can provide their creativity.